(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
HDFC Standard Life insurance is the oldest life insurance company in the world. It is the largest insurer in the UK and is the 28th largest company in the world. In India, the company is marketing life insurance products and unit linked investment plans. It has been found from the study that HDFC, SLIC has a lot of competition with other private insurers. The ideal premium would be between Rs. 5000 – Rs. 25000 and an ideal policy term would be 10 – 20 years.